Strengthening the Musical Literacy of High School Students with the Help of Computers - Odinakhan Mamirova (Journal of Learning on History and Social Sciences, 2024)
Taking into account that musical-theoretical knowledge is fully imparted only in specialized music schools, determining the forms and methods of imparting musical-theoretical knowledge in these educational institutions makes it possible to use them in general secondary educational institutions in the future. The article describes the strengthening of music literacy of high school students with the help of a computer.